2015
DOI: 10.1002/ange.201504473
|View full text |Cite
|
Sign up to set email alerts
|

Finding the Most Catalytically Active Platinum Clusters With Low Atomicity

Abstract: On a subnanometer scale, an only one‐atom difference in a metal cluster may cause significant transitions in the catalytic activity due to the electronic and geometric configurations. We now report the atomicity‐specific catalytic activity of platinum clusters with significantly small atomicity, especially below 20. The atomic coordination structure is completely different from that of the larger face‐centered cubic (fcc) nanocrystals. Here, an electrochemical study on such small clusters, in which the atomici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 35 publications
0
42
0
Order By: Relevance
“…Stable metal particles with enhanced catalytic activity strongly depend on the presence of single atoms or, vice-versa, of single vacancies. Investigations of nonmagic-number clusters in noble metals with 'with low atomicity' have just begun, i.e., by exploiting new synthesis methods promising the required single-atom precision in platinum clusters [24]. The results presented here substantially augment the ability to simulate the stability of such low-N metallic nanosystems.…”
Section: Introductionmentioning
confidence: 87%
“…Stable metal particles with enhanced catalytic activity strongly depend on the presence of single atoms or, vice-versa, of single vacancies. Investigations of nonmagic-number clusters in noble metals with 'with low atomicity' have just begun, i.e., by exploiting new synthesis methods promising the required single-atom precision in platinum clusters [24]. The results presented here substantially augment the ability to simulate the stability of such low-N metallic nanosystems.…”
Section: Introductionmentioning
confidence: 87%
“…Nanoclusters with a high volume/surface ratio and quantum effect have been proven to be efficient catalysts in various useful reactions. To date, several synthetic approaches have been developed to fabricate these small nanoparticles, including solution-phase reduction, gas-phase synthesis, and the ligand-assisted approach [25][26][27][28][29]. However, the fabrication of small nanoparticles is still challenging because of their severe aggregation, wide size distribution, low output, and low activity.…”
Section: Introductionmentioning
confidence: 99%
“…2 nm until Yamamoto, Imaoka et al . found that sub-nanosized Pt clusters showed extremely high ORR activities 6789…”
mentioning
confidence: 99%
“…However, the geometries of sub-nanosized Pt clusters have not been observed directly. Scanning transmission electron microscopy, for example, can measure only two-dimensional geometries of sub-nanosized clusters7. Therefore, their electronic structures and the relationship between their structures and catalytic activities are unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation